Discriminación y racismo en América Latina - KLICH, Ignacio comp. (NUEVO HACER, 1997)
Otros descriptores: NAZISMO; NAZIS; MEXICO; FRANCO, Francisco; HOLOCAUSTO.Colaboradores:MARTINEZ SARASOLA, Carlos; KLIMOVSKY, Gregorio; MARMORA, Lelio; CLEMENTI, Hebe; AUZA, Néstor Tomás; JOZAMI, Gladys; BARGMAN, Daniel; GIBERTI, Eva; BIALOGORSKY, Mirta; KNECHER, Lidia; PENKOWER, Monty Noam; LESSER, Jeffrey; LEVINE, Robert; GOJMAN DE BAXCKAL, Alicia; BOTANA, Natalio; SENKMAN, Leonardo; AVNI, Haim; LASERRE, Andre; MARQUINA BARRIO, Antonio; SCHWARZTEIN, Dora; BUCHRUCKER, Cristian; REIN, Raanan; GRAVIL, Roger; NEWTON, Ronald; WARSZAWSKI, Paul